The productions of animal-assisted activities as an alternative therapy in cancer patients (Research, Society and Development, 2022)
.The Animal-Assisted Therapy is a very old technique that prevails even today, with the aim of bringing well-being to hospitalized people undergoing treatment against various diseases, especially cancer. Providing many benefits, as many researches prove that cancer is a disease that greatly affects the emotional and psychological part of people. This work aimed to make a bibliographic survey focusing on the studied theme, especially cancer, using the dog. This study allowed us to conclude the possibility of minimizing the symptoms caused by cancer. Because experts guarantee that contact with the dog contributes to the improvement of physical and mental health, and even the resolution of various pathologies.